The impact of interest rate ceilings on households’ credit access: Evidence from a 2013 Chilean legislation - Madeira, Carlos (Journal of Banking & Finance, 2019)
This study analyzes the impact of a legislation introduced in Chile in 2013, which gradually reduced the maximum legal interest rate for consumer loans from 54% to 36%. Using a representative sample of households that matches survey data and banking loan records, I compare consumers with risk-adjusted interest rates slightly above and slightly below the legal interest rate ceiling, two groups of similar characteristics but who are differently affected by the law. After accounting for both macroeconomic shocks and unobserved household heterogeneity, the results show that being above the interest rate cap reduces the probability of credit access by 8.7% on average. A counterfactual exercise shows that the new legislation excluded 9.7% of the borrowers from banking consumer loans. The law’s impact was strongest on the youngest, least educated and poorest families. Finally, I show that the new law affected all lenders of consumer loans in Chile, not just banks.